2014
DOI: 10.5194/bg-11-4897-2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the spatial variability in peak season CO<sub>2</sub> exchange characteristics across the Arctic tundra using a light response curve parameterization

Abstract: Abstract. This paper aims to assess the spatial variability in the response of CO 2 exchange to irradiance across the Arctic tundra during peak season using light response curve (LRC) parameters. This investigation allows us to better understand the future response of Arctic tundra under climatic change. Peak season data were collected during different years (between 1998 and 2010) using the micrometeorological eddy covariance technique from 12 circumpolar Arctic tundra sites, in the range of 64-74 • N.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…It is also expected to lead to more efficient resorption of nutrients (Estiarte and Peñuelas 2014). Furthermore, earlier onset-of-senescence in an Arctic plant community changes the duration of peak season length, which corresponds to the period of maximum carbon uptake (Richardson et al 2009, Mbufong et al 2014. The length of peak season as well as the entire growing season is linked to various metrics of productivity in deciduous ecosystems (White et al 1999, Aurela et al 2004, Dragoni and Rahman 2012.…”
Section: Change In Timing and Rate-of-senescencementioning
confidence: 99%
“…It is also expected to lead to more efficient resorption of nutrients (Estiarte and Peñuelas 2014). Furthermore, earlier onset-of-senescence in an Arctic plant community changes the duration of peak season length, which corresponds to the period of maximum carbon uptake (Richardson et al 2009, Mbufong et al 2014. The length of peak season as well as the entire growing season is linked to various metrics of productivity in deciduous ecosystems (White et al 1999, Aurela et al 2004, Dragoni and Rahman 2012.…”
Section: Change In Timing and Rate-of-senescencementioning
confidence: 99%
“…Once the snow melts, the growing season (i.e. the part of the year when the weather conditions allow plant growth) has been reported as the most relevant period defining both spatial (Lund et al, 2010;Mbufong et al, 2014) and temporal (Aurela et al, 2004;Groendahl et al, 2007;Lund et al, 2012) CO 2 variability. The EC measurements were conducted at the EddyFen station (Fig.…”
Section: Measurementsmentioning
confidence: 99%
“…Different eco-types are linked to different C exchange rates (Bubier et al, 2003). Synthesis studies have found a significant spatial variability in NEE Mbufong et al, 2014) between different tundra sites Lund et al, 2010) and also large temporal variability within sites (Aurela et al, 2004Christensen et al, 2012;Grøndahl et al, 2008;Lafleur et al, 2012). Minor variations in the key process of photosynthesis (gross primary production, GPP) and ecosystem respiration (R eco ) may promote important changes in the sign and magnitude of the C balance (Arndal et al, 2009;Elberling et al, 2008;IPCC, 2007;Lund et al, 2010;Tagesson et al, 2012;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assumptions of flux homogeneity tend to rely on a qualitative and/or quantitative assessment of the spatial variability in some visible properties of the vegetation. However, this assumption ignores many difficult to measure factors known to vary spatially and influence C fluxes (Peukert et al, 2013;Glendell et al, 2014;Mbufong et al, 2014). It also ignores the evidence from both chamber and EC studies which have observed intra-ecosystem spatial variability of fluxes (Katul et al, 1999;Bubier et al, 2003;Oren et al, 2006;Riveros-Iregui & McGlynn, 2009;Peltola et al, 2015).…”
Section: Introductionmentioning
confidence: 99%